Safe Nurse Staffing and the 2022 AWHONN Nurse Staffing Standards. Issue 5 (September 2022) - Simpson, Kathleen Rice
Abstract : In June 2022, the Association of Women's Health, Obstetric, and Neonatal Nurses published updated standards for nurse staffing covering the continuum of inpatient childbirth and neonatal care. Since the first edition, published in 2010, there has been a substantial amount of evidence linking nurse staffing to patient outcomes. Safe, high-quality maternity care requires the appropriate number of nurses to provide comprehensive assessment, interventions as needed, emotional and physical support, and discharge teaching. Adequate nurse staffing can be a key factor in avoiding failure to rescue events and preventable adverse outcomes for mothers and babies hospitalized during the childbirth process.